Asynchronous programming easier asynchronous programming with the new Visual Studio Async CTP. IN Features. - Lippert, Eric.
The next version of C# and Visual Basic will include a form of asynchronous control flow that avoids both the dangers of multithreading and the pain of writing callback methods.
Keywords: Microsoft Visual studio; C# (Computer program language); Microsoft Visual BASIC; Asynchronous programming; Async CTP